The Challenges and Opportunities of Energy Transition across Africa - (:unkn) unknown (My University, 2023)
The provision of energy infrastructure is essential for economic growth, social cohesion, and environmental sustainability. This paper served to evaluate the challenges associated with energy development and transition across the African continent and proffer opportunities for sustainable transition. Extensive use of documents, official data and statistics on different aspects of the African society was employed for this study. Exploratory documentary research materials, extant literature, publications, journals and articles on the current status of energy generation and delivery in Africa, the concept of renewable energy pathways, the need for energy transitions and the major strategies in place in Africa and around the world were important study areas for this work. Exploratory research method and systematic review approach were used to study the energy transition techniques, challenges and opportunities across Africa. Important research points were the concept of renewable energy pathways, the need for energy transitions, the major strategies in place in Africa and around the world to meet with the zero-carbon emission strategies of 2050, the future directions in energy provision—renewable energy development, economic diversification and energy-efficiency in Africa and the effects of energy transition on the social, political, economic and cultural spheres across Africa. Results obtained showed that energy transition in Africa is rapidly growing, though differently across the region, following huge investments made into the renewable energy sector, legislations and policies on the fossil fuel usage and carbon emission and introduction of better and more efficient systems. Nevertheless, the challenges reported in this studying plaguing the African energy transition come in five spheres: social, political, economic, technological and cultural. These challenges seem to be ancient, ubiquitous and multidimensional. Harnessing the opportunities in renew
Keywords: African Research